Camellia velutina (Theaceae, Sect. Chrysantha), a new species from northern Vietnam - Van The Pham (2021)
Camellia velutina V.T. Pham, V.D. Luong & Aver. found in Phu Tho province, northeastern Vietnam is described and illustrated. The comparison between the new species and closely related species is provided